THE KGB REPRISAL TOWARDS ZENOVIIA FRANKO IN THE CONTEXT OF THE CASE “BLOCK” (1971 – 1972) - PASKA, Bohdan (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is a comprehensive study of the reprisal towards the philologist Zenoviia Franko by the State Security Committee (KGB) in the context of the “general pogrom” of the Ukrainian dissident movement. Methodology of the Research. The methodological basis of the article is the principles of objectivity, comprehensiveness, continuity, and historicism. In the study the methods of analysis and synthesis, problem-chronological, retrospective, typology have been used, as well as and comparison of information from various sources. The scientific novelty consists in the introduction into scientific circulation of a set of little-known documents from the State Archives of the Security Service of Ukraine (SBU), which enable us to reveal the prerequisites, course and results of the Soviet regime’s reprisal towards Z. Franko. For the first time, in the article there has been carried out a comprehensive analysis of the KGB’s measures against the linguist in 1971 – 1972. Conclusions. Thus, at the turn of the 1960s and 1970s, a linguist Z. Franko was one of the socially active participants in Kyiv dissident community. She was engaged in the distribution of samvydav publications, collecting funds for the public treasury, and making contacts with the Ukrainian diaspora. In July of 1971, after the dissident was included in the group development case “Block”, the KGB officers significantly intensified operational work against her using an agent network and a wiretapping system. In January of 1972, during the wave of arrests, it was decided to use preventive measures to achieve Z. Franko’s cooperation with the KGB, to obtain the necessary evidence against like-minded people from her, and completely compromise the dissident. The KGB’s special operation to discredit Z. Franko and isolate her from the resistance movement was complete success. Z. Franko’s penitential statement and subsequent appearance on television and radio were among the serious achievements of the special services at the initial stage of the “Block” case. The philologist’s testimony was actively used against the arrested dissidents, and her “renunciation” was a painful blow to the morale of the dissident community. In the following years, the linguist, temporarily deprived of her authority, withdrew from dissident activity and was forced to maintain close contacts with the KGB. Z. Franko was able to return to active participation in the national movement only during Gorbachev’s perestroika in the late 1980s. Key words: Zenoviia Franko, Ukrainian dissident movement, Committee for State Security (KGB), Soviet regime, repressions, “Block” case.